The Important Role of Reference Group in Smoking Behavior Demarketing Model - Muhammad Johan Widikusyanto; Pertiwi , Widya Nur Bhakti; Purbohastuti, Arum Wahyuni; Ika Putri, Solehatin (PT Larva Wijaya Penerbit, 2024)
Smoking behavior is one of the main causes of death from dangerous diseases in various countries, including Indonesia, which records more than 200 thousand deaths per year. To reduce cigarette consumption, a demarketing strategy can be applied with the aim of reducing the demand for dangerous products. This study aims to develop a more complete smoking behavior demarketing model, including the variables Product, Price, Place, Promotion, Reference Group, Attitude towards smoking, and Smoking behavior. This study also formulates a demarketing strategy based on the results of testing the model. Several relationships between variables, such as the influence of the marketing mix (4Ps) and reference groups on smoking attitudes and behavior, still lack empirical exploration. Previous studies also tend to stop testing smoking intentions without directly measuring smoking behavior. This study fills the gap by adding reference groups as important variables and directly testing the influence of various variables on smoking behavior. The questionnaire was distributed to active smokers with a total of 592 smokers. Furthermore, the data collected was analyzed using SEM. The research findings show that product, price, promotion, and reference group influence smoking attitudes and behavior. While the place has no effect. Meanwhile, price influences smoking attitudes, but not smoking behavior. It appears that reference groups have the greatest influence on smoking behavior followed by promotion. Based on these findings, several strategies can be formulated to suppress smoking behavior. Keywords: demarketing, marketing mix, reference group, smoking attitude, smoking behavior.